Analisis Kebutuhan Sistem Akreditasi Rumah Sakit di Indonesia dengan Metode Six Sigma - Gea, Diyurman; Jesica, Sharon (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This study aims to create a system that can support the implementation of the accreditation of the Hospital (RS) in Indonesia. Successful implementation of hospital accreditation in Indonesia is still far from the target that has been set, this is due to the geographical location factors and the limited availability of infrastructure. For successful implementation of this accreditation, it must be supported by a web-based application, which can be accessed by interested parties, such as the manager of the hospital, Surveyor, Commission on Hospital Accreditation Secretariat (KARS) and people who want to see the results of hospital accreditation. The proposed system is a system design that is capable of storing transaction data assessment, in accordance with the standards of the assessment element KARS. Documenting assessment can be made online or offline through the use of an excel file with a standardized format. Monitoring the implementation of accreditation can be determined quickly and accurately through the system reports. To find out the needs of the system, in-depth study conducted through interview techniques, analysis of documents and procedures that are running, as well as through discussion forums with the management team Surveryor KARS and Accreditation System. The data collected will be analyzed dengen Six Sigma method. The design of the system is described in the form of a data flow diagram, activity diagram and design Entity Relation Diagram (ERD). The proposed system will have an impact on improving the cost efficiency of infrastructure, data integration, accessibility and ease of monitoring the implementation of accreditation as well as guarantee the availability of data.